PERENCANAAN DAN STRATEGI PEMBELAJARAN FAHM AL-MASMŪ' DI MADRASAH - Mahyudin Ritonga; Muhammad Ali; Muhammad Jalel Ritonga (STIQ Amuntai, 2023)
Fahm al-masmu' is part of Arabic linguistic studies that are not familiar to academics in Arabic language education. This unpopularity then impacts learning, so doing a descriptive study of how the planning and learning strategies of fahm al-masmu' is important. Therefore, this study aims to reveal the planning and learning strategies of fahm al-masmu'. This study is literature research, and data sources are collected from various literature that contains research content both in the form of books and journals. To assist researchers in finding and analyzing data, publish or perish and Vosviewer tools are used. The use of this platform is intended to facilitate researchers in finding data and content. The results of this study are fahm al-masmu' learning planning is carried out by considering learning objectives, students, environmental conditions that are not noisy, existing learning resources, learning media and learning methods used. Fahm al-masmu's learning planning, which is prepared by considering various aspects holistically will help achieve listening skills for students.